Developing assessment model for bandel attitudes based on the teachings of Ki Hadjar Dewantara - Restituta Estin Ami Wardani; Supriyoko Supriyoko; Yuli Prihatni (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
The study was aimed at (1) identifying indicators for bandel attitudes in the teachings of Ki Hadjar Dewantara, and (2) finding out the results of the implementation of the developed bandel attitude assessment instrument. The study was developmental research in the affective domain using Mardapi’s ten developmental steps. Subjects were selected by cluster random sampling of 392 junior secondary school students, 57 for the limited-scale try-out and 335 for the wider-scale try-out. The data analysis techniques included those for Aiken content validity, concurrent validity, and Cronbach Alpha reliability. Data for the instrument implementation were analyzed using descriptive statistics. Findings show that (1) there are six indicators for the bandel instrument to be developed in a self-assessment questionnaire format of 24 items consisting of 12 common statements and 12 factual statements; all items are valid and reliable; (2) Students’ score in the implementation of the bandel assessment instrument is categorized into the very high level.